Mastering Speaking English And Implementation of Communication Hospitality Skills on Museum Guide Service in Bandung - Septy Indrianty; Nova Riana (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The implementation of tourism requires the ability of good service providers in terms of interacting with visitors.Â  Especially if the tourist destination is a destination that has the potential to receive guests/visitors from various nations. So in providing services to tourists, it is necessary to master English and Hospitality communication, which prioritizes hospitality. This study aims to determine the mastery of English and also the implementation of hospitality communication in museum guide services. The method used is descriptive qualitative by describing the depth of the data. Data collection was carried out in 3 ways: observation, interviews, and distributing questionnaires to 20 respondents consisting of museum guides and educators. The results of the study found that the guides' mastery of English in terms of the 4 speaking elements was in the "quite good" category with an average of 3.28. From the application of hospitality communication, it was found that museum guides had carried out courtesy in the excellent category with an average of 4.63 and an understanding of grooming in the good category with an average of 3.22.Â